Analisis Pemberdayaan Bank Sampah dalam Kerangka Ekonomi Sirkular: Pendekatan Teori ACTORS di Kota Tanjungpinang - Yulia, Yulia; Safitri, Dian Prima; Azizi, Okky Rizki (Indonesian Journal Publisher, 2025)
This study aims to analyze the empowerment of waste banks in Tanjungpinang City within a circular economy framework to support sustainable waste management. The study used a qualitative approach with a phenomenological method. The research location focused on three waste banks: the Main Waste Bank Berseri, the Kuantan Bersih Unit Waste Bank, and the Kembar Mandiri Unit Waste Bank. Data analysis used the ACTORS theory (Authority, Confidence and Competence, Trust, Opportunity, Responsibility, and Support) to understand the dynamics of community empowerment. The results showed that the three waste banks implemented empowerment through increasing manager capacity, environmental education, and circular economy-based waste management innovation. Empowerment was characterized by increased manager authority, social trust, and cross-sector support. The main challenges include budget constraints, low community participation, and fluctuations in recycling prices. This study recommends strengthening waste bank institutions, expanding cross-sector partnerships, and improving environmental education. Socially, empowerment through waste banks can foster ecological awareness and community economic independence. This study integrates ACTORS theory and the circular economy concept to explain environmentally based community empowerment, demonstrating that waste banks function as a means of social transformation toward participatory and sustainable environmental governance.